Capital requirements, monetary policy and risk shifting in the mortgage market - Uluc, Arzu; Wieladek, Tomasz (Journal of Financial Intermediation, 2018)
We study the effect of changes to bank-specific capital requirements on mortgage loans with a new loan-level dataset containing all new mortgages issued in the UK between 2005Q2 and 2007Q2. We find that a rise of a 100 basis points in capital requirements leads to a 4% decline in individual mortgage loan size. Borrowers with an impaired credit history (verified income) are not (most) affected. This is consistent with the origination of riskier loans to grow capital by raising retained earnings. We then examine the interaction of capital requirements and monetary policy. This suggests that a monetary policy tightening may mitigate the loan contraction associated with higher capital requirements, as maturity transformation allows the affected bank to profit from a steeper yield curve and raise capital through retained earnings. Overall, our findings in this paper indicate that retained earnings are an important channel of adjustment to capital requirements.